Novel Genetic Variants Associated With Increased Vertebral Volumetric BMD, Reduced Vertebral Fracture Risk, and Increased Expression of SLC1A3 and EPHB2. (6th September 2016) - Nielson, Carrie M; Liu, Ching‐Ti; Smith, Albert V; Ackert‐Bicknell, Cheryl L; Reppe, Sjur; Jakobsdottir, Johanna; Wassel, Christina; Register, Thomas C; Oei, Ling; Alonso, Nerea; Oei, Edwin H; Parimi, Neeta; et al.
ABSTRACT: Genome‐wide association studies (GWASs) have revealed numerous loci for areal bone mineral density (aBMD). We completed the first GWAS meta‐analysis ( n  = 15, 275) of lumbar spine volumetric BMD (vBMD) measured by quantitative computed tomography (QCT), allowing for examination of the trabecular bone compartment. SNPs that were significantly associated with vBMD were also examined in two GWAS meta‐analyses to determine associations with morphometric vertebral fracture ( n  = 21, 701) and clinical vertebral fracture ( n  = 5893). Expression quantitative trait locus (eQTL) analyses of iliac crest biopsies were performed in 84 postmenopausal women, and murine osteoblast expression of genes implicated by eQTL or by proximity to vBMD‐associated SNPs was examined. We identified significant vBMD associations with five loci, including: 1p36.12, containing WNT4 and ZBTB40 ; 8q24, containing TNFRSF11B ; and 13q14, containing AKAP11 and TNFSF11 . Two loci (5p13 and 1p36.12) also contained associations with radiographic and clinical vertebral fracture, respectively. In 5p13, rs2468531 (minor allele frequency [MAF] = 3%) was associated with higher vBMD (β = 0.22, p  = 1.9 × 10 –8 ) and decreased risk of radiographic vertebral fracture (odds ratio [OR] = 0.75; false discovery rate [FDR] p  = 0.01). In 1p36.12, rs12742784 (MAF = 21%) was associated with higher vBMD (β = 0.09, p  = 1.2 × 10 –10 ) and decreased risk of clinical vertebral fracture (OR = 0.82; FDR p  = 7.4 × 10 –4 ). Both SNPs are noncoding and were associated with increased mRNA expression levels in human bone biopsies: rs2468531 with SLC1A3 (β = 0.28, FDR p  = 0.01, involved in glutamate signaling and osteogenic response to mechanical loading) and rs12742784 with EPHB2 (β = 0.12, FDR p  = 1.7 × 10 –3, functions in bone‐related ephrin signaling). Both genes are expressed in murine osteoblasts. This is the first study to link SLC1A3 and EPHB2 to clinically relevant vertebral osteoporosis phenotypes. These results may help elucidate vertebral bone biology and novel approaches to reducing vertebral fracture incidence. © 2016 American Society for Bone and Mineral Research.